2006
DOI: 10.1007/s00339-006-3578-0
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure of 1,2-PCB10H11 molecular films: a precursor to a novel semiconductor

Abstract: Boag, N.M.; Nelson, K.; Montag, B.; Brand, Jennifer I.; and Dowben, Peter A., "The electronic structure of 1,2-PCB 10 H 11 molecular films: a precursor to a novel semiconductor" (2006 Abstract: The band gaps and electronic structure of un doped fi lms of molecular icosahedra of closo-1-phospha-2 carbadodecaborane (1,2-PCB 10 H 11 ) are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 55 publications
(120 reference statements)
3
50
0
Order By: Relevance
“…18 This PECVD approach is well established and has been successful in the fabrication of both heterojunction [1][2][3][4]16,17,21 junction diodes 14,15,18 of boron carbide as well as diodes made from two polytypes of boron carbide. [5][6][7]21 X-ray photoemission spectroscopy ͑XPS͒ confirmed that cobalt is indeed incorporated in C 2 B 10 H x boron carbide films after cobaltocene decomposition, in films formed from both metacarborane and cobaltocene decompositions. From the relative XPS intensities, we estimate that there is only about 0.5%-1.5% cobalt ͑or less͒ in these C 2 B 10 H x films.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This PECVD approach is well established and has been successful in the fabrication of both heterojunction [1][2][3][4]16,17,21 junction diodes 14,15,18 of boron carbide as well as diodes made from two polytypes of boron carbide. [5][6][7]21 X-ray photoemission spectroscopy ͑XPS͒ confirmed that cobalt is indeed incorporated in C 2 B 10 H x boron carbide films after cobaltocene decomposition, in films formed from both metacarborane and cobaltocene decompositions. From the relative XPS intensities, we estimate that there is only about 0.5%-1.5% cobalt ͑or less͒ in these C 2 B 10 H x films.…”
Section: Methodsmentioning
confidence: 99%
“…20͒ are not n-type dopants for boron carbide either, if they are even dopants in the conventional sense at all. Phosphorus, like cobalt, also may 21 or may not 19 be a n-type dopant of boron carbide. If cobalt is a successful dopant two questions surface, beyond those related to the question of the majority carrier introduced by cobalt doping: is the doping random, i.e., dilute, 22,23 or do the dopants cluster as has been observed for cobalt dopants in some oxide dielectrics?…”
Section: Introductionmentioning
confidence: 99%
“…This latter all boron carbide device has been described as a heteroisomeric diode [4], as two electronically different semiconducting boron carbide polytypes are used, and the diode is not quite a conventional homojunction diode, although the two semiconducting boron carbides are compositionally similar. More recently, an all boron carbide heterojunction diode has been fabricated using two very different types of boron carbide [27]. All three types of diodes behave reasonably similar, with similar diode characteristics.…”
mentioning
confidence: 99%
“…All boron carbide p-n junction diodes were also fabricated by chemical vapor deposition from two different isomers of closo-dicarbadodecaborane (closo-1,2-dicarbadodecaborane (orthocarborane, C 2 B 10 H 12 ) and closo-1,7-dicarbadodecaborane (metacarborane, C 2 B 10 H 12 )) that differ only by the carbon position within the icosahedral cage. The diodes were constructed using the process of PECVD (plasma enhanced chemical vapor deposition) as described for both heterojunction [1,[25][26][27][28][29][30] and homojunction diodes [25,26] of boron carbide, but with only carboranes and argon as the plasma reactor gases. The boron carbide semiconductor fi lms formed after decomposition are clearly self doping materials, since the deposition and decomposition involves only the metacarborane and orthocarborane source molecules (n-type and p-type, respectively), as discussed elsewhere [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation